The Influence of Work Climate, Work Discipline, and Workload on Employee Job Satisfaction at the Environmental and Forestry Service of the Special Region of Yogyakarta. - Jenny Anggela; Syamsul Hadi; Tri Ratna Purnamarini (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2025)
This study aims to determine the effect of work climate, work discipline, and workload on employee job satisfaction at the Environmental and Forestry Service of the Special Region of Yogyakarta. The method used in this study is quantitative with a sampling method, namely Nonprobability Sampling or saturated sampling technique at the Environmental and Forestry Service of the Special Region of Yogyakarta as many as 76 respondents. Data collection was carried out through a questionnaire with data processing using SPSS 25 which was used as a data analysis tool. The results of the study showed that work climate had a positive and significant effect on job satisfaction, work discipline had a positive and significant effect on job satisfaction, and workload had a positive and insignificant effect on job satisfaction. Then work climate, work discipline, and workload simultaneously influenced the job satisfaction of employees of the Environmental and Forestry Service of the Special Region of Yogyakarta.